Participation in the Student Committee at the Brazilian Nursing Association: experience report (Research, Society and Development, 2022)
Objective: To report the experience of the participation of active and inactive members of the Student Committee in the Brazilian Nursing Association- Rio de Janeiro section (COEST ABEn-RJ). Method: This is a reflective study using an experience report, developed by a former member and current member of COEST-ABen-RJ. Result and discussion: Participating in a representative Student Movement of Nursing is to understand and analyze the entire context of ideas in which a particular group is inserted. COEST is the most efficient means of communication between nursing students of all levels and ABEn RJ. The realization of scientific events by the student fosters the scenario of academic production and generates discussions and visibility on the subject. Final considerations: It is understood that COEST is an instrument for truly transformative changes, where the object, in this case, the focus of attention, nursing students, when receiving interventions, produces questions and reflections for the benefit of the profession. The preservation of this space for the process of incorporation of the newly graduated student in the professional scope and its implications in the practices of nursing practice in relation to the type of knowledge aggregated not only at COEST, but at the nursing school is irrefutable.